Individual variation of bowstring release in high level archery: A comparative case study - Ertan, H.; Knicker, A. J.; Soylu, R. A.; Strüder, H. K. (Human Movement, 2011)
The muscle-contraction strategy between the predominant forearm and pull finger used in archery is defined as a response to the fall of the "clicker" by active contraction of the m. extensor digitorum (MED) and the gradual relaxation of the m. flexor digitorum superficialis (MFDS). However, one archer with a long-term high performance history makes use of an entirely different strategy, which is thought to have positive effects on her performance. The purpose of this study was to make a more detailed analysis of the contraction strategy performed by this particular top-level archer and to consider the advantages this strategy may have on bowstring behaviour after release. Methods. A high level (world-class) archer volunteered to participate in this study. The subject has been ranked in the top 20 in the world and as one of the top 3 archers in Europe for almost two decades. The subject has a personal best score of 1354 points (pts) in a qualification round as well as receiving 168 pts in an 18-arrow match. The subject engaged in a single test session consisting of 12 shots. EMG activity of the MFDS and MED were quantified. Results. The subject's MFDS was found to be clearly relaxed even ~ 100 ms after the snap of the clicker was heard. The subject also showed a gradual relaxation of the MED after the snap of the clicker. Conclusion. The study results found that this different type of contraction-relaxation strategy can be used in the drawing arm with success, as it may avoid causing a lateral deflection of the bowstring.